Validation of a ligand-binding assay for active protein drug quantification following the 'free analyte QC concept'. (December 2016) - Schick, Eginhard; Staack, Roland F; Haak, Markus; Jordan, Gregor; Dahl, Uwe; Heinrich, Julia; Birnboeck, Herbert; Papadimitriou, Apollon
Aim: Active drug assays are becoming increasingly important in protein drug development. We describe the validation of a ligand-binding assay for active protein drug quantification and address practical challenges as well as regulatory implications.Results: A bioanalytical method for active protein drug quantification was successfully validated. Validation data prove that this method can be routinely used applying the commonly accepted acceptance criteria for ligand-binding assays.Conclusion: Active drug assays are a powerful tool to elucidate the pharmacokinetic/pharmacodynamic relationship as they take into consideration the influence of various matrix components, such as soluble ligand and anti-drug antibodies. However, not all aspects of the validation concept described in the guidelines for pharmacokinetic assays can be applied to active drug assays and thus regulatory guidelines should be adapted in consequence.